Methyl (2Z)-2-({N-[2-(hydroxymethyl)phenyl]-4-methylbenzenesulfonamido}methyl)-3-phenylprop-2-enoate - R. Madhanraj (Acta Crystallographica Section E, 2012)
In the title compound, C25H25NO5S, the O atom of the hydroxy group is disordered over two positions, with occupancies of 0.820 (2) and 0.180 (2). The sulfonyl-bound benzene ring forms dihedral angles of 31.8 (1) and 60.7 (1)°, respectively, with the hydroxymethylbenzene and phenyl rings. The molecular conformation is stabilized by an intramolecular O—H...O hydrogen bond, generating an S(8) ring motif. The crystal packing is stabilized by intermolecular C—H...O hydrogen bonds and C—H...π interactions.